Developing a Green Business Model Canvas for Sustainable Waste Management: A Case Study of Banyumas Green Waste Innovation Center - Rochmat Purnomo; Siti Arifah; Dimitrios Tsagdis; Sri Martani Effiyanti (Review of Applied Accounting Research (RAAR), 2026)
Effective waste management remains a significant environmental challenge in Indonesia, where conventional landfills frequently reach capacity and improper disposal contributes to pollution and greenhouse gas emissions. In Banyumas Regency, the Unit Pelaksana Teknis Tempat Pengolahan Sampah Terpadu Berbasis Lingkungan & Edukasi (UPT TPST-BLE) presents an innovative approach, integrating advanced waste processing technologies with community-focused initiatives to transform waste into valuable resources such as maggot feed, kasgot, compost, paving blocks, tiles, and biodiesel from used cooking oil. This study employs a qualitative case study method, combining direct observation, in-depth interviews with management, staff, and stakeholders, and analysis of operational documents to design a sustainable business framework using the Triple Layer Business Model Canvas (TLBMC). Findings indicate that UPT TPST-BLE has successfully implemented an integrated waste management system, generating economic gains through diversified product sales, empowering local communities, and substantially reducing landfill dependence and greenhouse gas emissions. Critical success factors include strong local government support, partnerships with private enterprises, and ongoing public education. The research offers practical insights for policymakers and waste management practitioners, demonstrating how technological innovation, stakeholder engagement, and a diversified product portfolio can foster sustainable waste management that delivers economic, social, and environmental benefits in developing country contexts.